Penerapan Differentiated Instruction dalam Meningkatkan Hasil Belajar Peserta Didik di Kelas Inklusif (UNIB Press, 2024)
This community service activity aims to implement Differentiated Instruction (DI) at SDIT Nuriz to improve inclusive classroom practices. This activity includes two-day training for teachers, six-week implementation of DI in class VI-B, and monitoring and evaluation. The results showed that 90% of teachers were more confident in implementing DI, with 85% of class activities in accordance with DI principles. The implementation of DI increased the average student test score by 14.3% and understanding of the material by 23.1%. Teacher satisfaction with the training and implementation of DI reached 88% and 85%, respectively. Future recommendations include expanding DI training and a more comprehensive evaluation of its impact on inclusive education.